Algorithms for determining aquifer characteristics from pumping test data - Joshi, Surendra Govinda; Gupta, Ashim Das; Anat Arbhabhirama; Suphat Vongvisessomjai; Prida Thimajorn; Carl Duisberg Gesellschafte.v. , West Germany (Bangkok : Asian Institute of Technology, 1981)
Algorithms are developed with a view of the least square error approach in estimating aquifer characteristics for predicting time drawdown relationship by using pumping test data. The cases of pumping test with observation wells and single well step pumping test are dealt with separately. A study is also made of some of existing procedures of predicting time drawdown relationship. For the analysis of pumping test data with observation wells, a simulation technique based on an existing widely accepted graphical procedure is adopted to approach the least square error in observed and computed drawdown. A number of cases are analyzed with the code BESTFTT and comparisons are made with the existing methods. An existing computer method (FASTEP), to evaluate the well characteristics from a single well step pumping test at constant time interval, is compared with the algorithm REGFIT developed for that case by analyzing five different data sets. Visualizing the erroneous assumptions in the existing expression of drawdown for a constant interval of time, an introduction of 'adjusted time ' is made in the general expression of drawdown for any time to validate the assumptions. Algorithm SINGLE is presented to compute the adjusted time. Modified REGFITM and FASTEPM are put forward to estimate the well characteristics using output of SINGLE. A simple digital code PREDICT is also presented to compute the drawdowns for a desirable pumping rate for 24 hours. The digital method BESTFIT is more effective than existing methods of determining time - drawdown relationship from the observed pumping test data. FASTEP is superior to REGFIT developed. It may be the result of erroneous assumptions in the expression of drawdown for constant interval of time. Computer code SINGLE could be successfully applied to the practical problems in obtaining basis for determining aquifer characteristics from a single well step pumping test data. In addition, prediction of drawdowns for any time and pumping rate could be made using REGFITM or FASTEPM and PREDICT.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Aquifers -- Mathematical models